Commercial Bank Stimulus on Economic Growth and Labour Absorption in Indonesia - Irawan, Irawan; Kusuma, Rio Dhana; Irawan, Kevin Chandida (Journal of Economic Education, 2021)
This study aims to find out the effect of Commercial Bank credit on Economic Growth and Labour Absorption in Indonesia. The data source used was secondary data obtained through the publication of the Central Bureau of Statistics, Bank Indonesia, and the Financial Services Authority. The method of data collection is the periodic report data (time series) for the years 2007-2017. The analytical tool used quantitative analysis. The data analysis technique used path analysis. The results show that: 1) Commercial bank credit has a direct and significant effect on economic growth in Indonesia; 2) Commercial bank credit has a direct and significant effect on labour absorption in Indonesia; 3) Commercial bank credit does not have a significant effect on labour absorption through economic growth in Indonesia; 4) Economic growth does not have a direct and significant effect on labour absorption in Indonesia